Pengaruh Pengelolaan Aktiva, Kebijakan Utang, dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Sub Sektor Transportasi dan Logistik di Bursa Efek Indonesia Tahun 2019-2024 - Afifah Izza; Usdeldi Usdeldi; Muthmainnah Muthmainnah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine and analyze the effect of asset management, debt policy, and dividend policy partially and simultaneously on company value in the Transportation and Logistics Sub-Sector on the Indonesia Stock Exchange for the 2019-2024 period. The research approach used in this study is quantitative research. For the research sample of 37 companies listed on the Indonesia Stock Exchange, only seven companies in the transportation and logistics sub-sector met the criteria for this study. This is because only seven companies listed on the main board and acceleration meet the requirements set by the researcher. The results of this study indicate: 1) That asset management has a positive and significant effect partially on company value. 2) Debt policy has a negative and significant effect partially on company value. 3) Dividend policy does not have a partial effect on company value. 4) Then asset management, debt policy, and dividend policy have a simultaneous effect on company value in the Transportation and Logistics sub-sector on the Indonesia Stock Exchange for the 2019-2024 period